Isolated falciparum ligament necrosis causing right upper quadrant pain - Koca, Yavuz Savaş; Okur, Nazan; Barut, İbrahim (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Koca YS, Okur N, Barut İ. Isolated falciparum ligament necrosis causing right upper quadrant pain. Turk J Gastroenterol 2017; 28: 531-2.